(untitled) (International Journal of Environmental Sciences, 2025)
The tourism industry has become one of the potential revenues for local governments in many regions. It may transform the local economy from a traditional based into a promising economic welfare for local society if managed properly. However, this transformation process may also require a proper tourism development policy to increase the attractiveness of tourism destinations to increase tourist visits. This paper is intended to evaluate the implementation of tourism development master plan to increase tourist visits in Wasur National Park, Merauke Regency of Indonesia. It is descriptive research that is applied through a qualitative approach aimed to explore on “how” and “why” the effort to develop Wasur National Park seems to meet its stagnation process during the policy implementation phase. The result of this study confirms two primary findings, first, the implementation of tourism development policy in Wasur National Park is hampered by multiple interests within a single policy implementation. It triggered asymmetric commitment among stakeholders and led to the separate movement of program implementation. Second, each institution tends to perform different strategies with one policy framework which generates ineffective policy outcomes